Nutritional assessment - Lee, Robert D. 1952-; Nieman, David C. 1950- (New York McGraw-Hill, 2013)
"This text describes the four major methods of nutritional assessment (dietary, anthropometric, biometric, and clinical) in an understandable and contemporary way. It thoroughly covers assessment of the hospitalized individual, but also serves as an invaluable resource to the nutrition professional working in such areas as public health and community nutrition, corporate health, and sports medicine"-- Provided by publisher.
Machine generated contents note: 1. Introduction to Nutritional Assessment ; 2. Standards for Nutrient Intake ; 3. Measuring Diet ; 4. National Dietary and Nutrition Surveys ; 5. Computerized Dietary Analysis Systems ; 6. Anthropometry ; 7 Assessment of the Hospitalized Patient. 8. Nutritional Assessment in Disease Prevention. 9. Biochemical Assessment of Nutritional Status. 10. Clinical Assessment of Nutritional Status11 Counseling Theory and Technique. -- Appendix A. Nutrition Assessment and Monitoring and Evaluation Terminology. Appendix B. Nutrition Diagnostic Terminology. Appendix C. Nutrition Intervention TerminologyAppendix D. Food Record Recording Form -- Appendix E. Fruit and Vegetable Screener Developed by the U.S. National Cancer Institute. Appendix F. MEDFICTS Dietary Assessment Questionnaire. Appendix G. The National Institute of Health's The Diet History Questionnaire II. -- Appendix H. The NHANES Food Frequency QuestionnaireAppendix I. 2011 Behavioral Risk Factor Surveillance System Questionnaire. -- Appendix J. Suppliers of Nutritional Assessment Equipment. -- Appendix K. CDC Clinical Growth Charts.
Includes bibliographical references and index.
Keywords: Nutrition surveys; Nutrition -- Evaluation; Nutrition disorders -- Diagnosis